Modal acoustic emission of damage accumulation in C/C–SiC composites with different fiber architectures. Issue 9 (November 2015) - Breede, Fabian; Koch, Dietmar; Maillet, Emmanuel; Morscher, Gregory N.
Abstract: The stress-dependent material behavior of carbon fiber reinforced ceramic matrix composites (C/C–SiC) was investigated with modal acoustic emission (AE) technique. AE observation is a promising health monitoring method which provides accurate location and identification of the recorded damage-related AE events. For a better understanding and identification of different damage mechanisms C/C–SiC composites with different fiber orientations were studied. Load/unload/reload tensile tests were performed and measurements were made over the entire stress range in order to determine the stress-dependence of acoustic activity for increasing damage states. In general it was found that in C/C–SiC composites a significant damage-related increase in AE energy was observed close to the ultimate tensile stress. Also, fiber architecture dependent differences during damage accumulation in terms of total number of AE events and their typical AE energy could be determined and correlated to different damage mechanisms.